STUDI SIMULASI PERHITUNGAN PENCAHAYAAN BUATAN DI DALAM BANGUNAN KOMERSIL MENGGUNAKAN APLIKASI ZHITOV BERBASIS WEBSITE (STUDI KASUS : TOKO GUDANG KOSMETIK PURWOKERTO) (Jurnal Arsitektur ARCADE, 2026)
Artificial lighting plays a pivotal role in commercial environments, extending beyond basic visual functionality to craft atmospheres that enhance the shopping experience and accentuate product aesthetics. This study aims to evaluate the performance of the existing artificial lighting system at Toko Gudang Kosmetik Purwokerto and assess the feasibility of the web-based application, Zhitov, as a computational simulation tool for lighting calculations. Using a descriptive quantitative approach based on building simulation, this research employed the Zhitov platform to analyze current lighting conditions based on existing building parameters. The performance was evaluated against the SNI 03-6197-2020 standard for energy conservation in building lighting systems. The results indicate that the existing lighting condition at the locus exhibits an average illuminance level of 170.172 lux. Through this computational analysis, the study successfully identified areas requiring improvement and proposed optimized design interventions—specifically comparing the total power consumption of 18 units of LED lamps (1710W), Neon lamps (4248W), and Incandescent lamps (17010W)—which are projected to achieve target illumination standards while significantly enhancing energy efficiency. This research affirms the utility of Zhitov as an effective simulation tool for environmental analysis and the optimization of artificial lighting design.
Keywords: Artificial Lighting, Lighting Simulation, Zhitov.ru, Commercial Building, SNI 03-6197-2020, Design Optimization